Deployment of a High Technology Readiness Level Electric Vehicle Charger - Espina-Gonzalez, E; Diaz-Diaz, M; Aravena-Carrasco, J (Institute of Electrical and Electronics Engineers Inc., 2024)
As the global automotive industry transitions to sustainable transportation, electric vehicles are expected to be the replacement for vehicles with internal combustion engines. To support the massification of EVs, Electric Vehicle Supply Equipments (EVSEs) will be required. This paper presents the design and implementation of an EVSE designed for alternating current charging. The proposed EVSE is composed of a real-time control system and control systems to provide user-friendly charging, targeting an advanced technology research level. Experimental results obtained from the charging of a commercial electric vehicle are presented demonstrating the effectiveness of the proposed EVSE in real-world conditions. © 2024 IEEE.